Stimuli-Responsive Nanocarriers for Site-Specific Drug Delivery System - Ankita Y.Gawai,; Pooja R. Hatwar,; Dr. Ravindra L. Bakal,; Krushnali N. Nehar,; Pranali R. Bhujade, (Asian Journal of Pharmaceutical Research and Development, 2025)
Stimuli-responsive nanocarriers have emerged as a promising tool for site-specific drug delivery, offering improved therapeutic efficacy and reduced side effects. These nanocarriers can respond to various internal and external stimuli, such as pH, temperature, light, and enzymes, to release therapeutic agents in a controlled manner. The design and synthesis of different types of stimuli-responsive nanocarriers, including liposomes, polymeric nanoparticles, micelles, and hydrogels, are discussed. The applications of these nanocarriers in cancer therapy, treatment of inflammatory arthritis, gene therapy, and management of neurological diseases are also explored. The benefits and challenges of using stimuli-responsive nanocarriers for site-specific drug delivery are highlighted, and future directions for research and development are outlined. The potential of stimuli-responsive nanocarriers to revolutionize the field of medicine by providing targeted and controlled drug delivery is emphasized.